Implementation of morbidity and mortality conference in a community hospital NICU and narrative review - Chan, Christina; Pazandak, Christine; Angelis, Dimitrios (Frontiers in Pediatrics, 2023)
BACKGROUND: The process of morbidity and mortality review (MMR) is recognized as an essential component of quality improvement, patient safety, attitudes towards patient safety, and continuing education. Despite the common use of MMR for all disciplines of medical care, recommendations have not been published regarding the implementation of MMR in a community hospital setting in the United States. OBJECTIVES: Review the literature on MMR conferences. Describe the implementation of an MMR conference in a community hospital neonatal intensive care unit (NICU). AUTHORS' CONCLUSIONS: The establishment of a case overview method of MMR is feasible for a community hospital NICU. It increases staff and physician group awareness and education over common and complex mortality and morbidity etiologies, improves staff participation with unit management, links case presentation with open discussion and action items, and identifies opportunities for systemic changes to improve patient care.